2017
DOI: 10.1111/jvh.12695
|View full text |Cite
|
Sign up to set email alerts
|

The role of peginterferon in nucleos(t)ide‐analogue‐treated chronic hepatitis B patients: A review of published literature

Abstract: Chronic hepatitis B infection (CHB) causes up to 1.0 million deaths annually. Currently, more than 90% of CHB patients worldwide are receiving indefinite nucleos(t)ide analogue (NA) therapy. New strategies for optimizing hepatitis B surface antigen (HBsAg) loss are required for NA-treated patients as the majority are unable to achieve HBsAg loss and may require lifelong therapy. In hepatitis B e antigen (HBeAg)-positive patients, switching from NAs to finite peginterferon (PegIFN) therapy can double HBeAg sero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Indeed, <5% of adult patients with CHB show cleared HBsAg after IFNa treatment, whereas over 50% of the children treated with PEG‐IFNa in our study achieved a functional cure. Generation of protective HBsAb is also rarely achieved in CHB adults and is therefore scarcely documented ; however, nearly half of the IFNa‐treated patients in our cohort generated a protective level of HBsAb. Overall, these results demonstrated a high level of status changes of HBV DNA, HBeAg, HBsAg and HBsAb in PEG‐IFNa‐treated individuals, indicating that children and adolescents with CHB are more responsive to PEG‐IFNa treatment to achieve a functional cure.…”
Section: Discussionmentioning
confidence: 82%
“…Indeed, <5% of adult patients with CHB show cleared HBsAg after IFNa treatment, whereas over 50% of the children treated with PEG‐IFNa in our study achieved a functional cure. Generation of protective HBsAb is also rarely achieved in CHB adults and is therefore scarcely documented ; however, nearly half of the IFNa‐treated patients in our cohort generated a protective level of HBsAb. Overall, these results demonstrated a high level of status changes of HBV DNA, HBeAg, HBsAg and HBsAb in PEG‐IFNa‐treated individuals, indicating that children and adolescents with CHB are more responsive to PEG‐IFNa treatment to achieve a functional cure.…”
Section: Discussionmentioning
confidence: 82%
“…Accordingly, a strong correlation between serum HBV RNA and cccDNA during treatment with NAs as well as with PegIFN alfa-2a was demonstrated in a recent study by Giersch et al [20]. Thus, serum HBV RNA may represent a reliable serum marker for cccDNA activity, and monitoring of serum HBV RNA levels may be a useful additional marker, particularly for future treatments aimed at cccDNA eradication [12].…”
Section: Discussionmentioning
confidence: 93%
“…While several treatment-stopping rules and responseguided therapy algorithms have been proposed [11], their main limitation is the relatively small proportion of nonresponders (approximately 20%) that are accurately identified [7,8]. Thus, exploration of novel response-predicting biomarkers is needed in order to improve the efficacy of PegIFN alfa treatment [12].…”
mentioning
confidence: 99%
“…Several randomized controlled trials reported 4–9.8% HBsAg seroclearance rates when NA was changed to 48-week peginterferon alfa treatment with/without maintaining NA [358-362]. In addition, 96-week peginterferon alfa treatment increased the HBsAg seroclearance rate to 15.3%.…”
Section: Management According To Treatment Responsementioning
confidence: 99%